A fundamental regulatory mechanism operating through OmpR and DNA topology controls expression of Salmonella pathogenicity islands SPI-1 and SPI-2 - DORMAN, CHARLES (My University, 2012)
DNA topology has fundamental control over the ability of transcription factors to access their target DNA sites at gene promoters. However, the influence of DNA topology on protein–DNA and protein–protein interactions is poorly understood. For example, relaxation of DNA supercoiling strongly induces the well-studied pathogenicity gene ssrA (also called spiR) in Salmonella enterica, but neither the mechanism nor the proteins involved are known. We have found that relaxation of DNA supercoiling induces expression of the Salmonella pathogenicity island (SPI)-2 regulator ssrA as well as the SPI-1 regulator hilC through a mechanism that requires the two-component regulator OmpR-EnvZ. Additionally, the ompR promoter is autoregulated in the same fashion. Conversely, the SPI-1 regulator hilD is induced by DNA relaxation but is repressed by OmpR. Relaxation of DNA supercoiling caused an increase in OmpR binding to DNA and a concomitant decrease in binding by the nucleoid-associated protein FIS. The reciprocal occupancy of DNA by OmpR and FIS was not due to antagonism between these transcription factors, but was instead a more intrinsic response to altered DNA topology. Surprisingly, DNA relaxation had no detectable effect on the binding of the global repressor H-NS. These results reveal the underlying molecular mechanism that primes SPI genes for rapid induction at the onset of host invasion. Additionally, our results reveal novel features of the archetypal two-component regulator OmpR. OmpR binding to relaxed DNA appears to generate a locally supercoiled state, which may assist promoter activation by relocating supercoiling stress-induced destabilization of DNA strands. Much has been made of the mechanisms that have evolved to regulate horizontally-acquired genes such as SPIs, but parallels among the ssrA, hilC, and ompR promoters illustrate that a fundamental form of regulation based on DNA topology coordinates the expression of these genes regardless of their origins.
PUBLISHED
Published online 22 March 2012
Keywords: DNA; DNA transcription; DNA-binding proteins; Gene expression; Polymerase chain reaction; Salmonella enterica; Topology; Genes & Society; Immunology, Inflammation & Infection